A Conceptual Exoskeleton Shoulder Design for the Assistance of Upper Limb Movement - Perez, Carlos Navarro; Georgilas, Ioannis; Etoundi, Appolinaire C.; Chong, Jj; Jafari, Aghil (Towards Autonomous Robotic Systems, 2018)
There is an increased interest on wearable technologies for rehabilitation and human augmentation. Systems focusing on the upper limbs are attempting to replicate the musculoskeletal structures found in humans, reproducing existing behaviors and capabilities. The current work is expanding on existing systems with a novel design that ensures the maximum range of motion while at the same time allowing for lockable features ensuring higher manipulation payloads at minimum energy and fatigue costs. An analysis of the biomechanics of the shoulder is being done and a detailed system design for structural as well actuation elements of a parallel mechanism is given. The benefits for the use are discussed of reduced weight, maximum range of motion at minimum energy cost.